Analysis on Cases of Public Library Service Innovation under the Background of Cultural and Tourism Integration - YUN Yun, LU Hejian (Nongye tushu qingbao xuebao, 2020)
[Purpose / Significance] In the context of the country's continuous construction and improvement of the public cultural service system and the integrated development of cultural and tourism, it is of great strategic significance for public libraries to seize the opportunity, actively explore innovative ways of services, and build public libraries into the places which promote in-depth and coordinated integrated development of culture and tourism. [Method / Process] The article briefly introduces the current status of the integrated development of the cultural and tourism services in public libraries in China, and analyzes the typical practice and existing problems of "public library + integration of culture and tourism" in China at the present stage. [Results / Conclusions] The paper puts forward suggestions: laying a solid foundation for the development of study tour courses; strengthening the digitization of resources and increasing the degree of information sharing; attaching importance to cultural connotation and guiding readers to read and learn; by innovative forms of publicity, promoting the popularity of libraries' cultural and tourism services; deeply exploiting libraries' collection resources and developing cultural and creative products with characteristics.